A Pharmacoepidemiological Evaluation Of Glycaemic Control Among Diabetes Patients Receiving Different Treatment Regimens At Penang General Hospital - Ibrahim, Kansaa A. (2010)

(untitled)
Generally, type 2 diabetes mellitus cannot be managed with a single drug or lifestyle changes alone; therefore, adding anti-diabetic agents or increasing the dose is recommended to control the disease progression. This study aimed to evaluate the antidiabetic drugs used at Penang General Hospital in relation to the clinical outcomes of the disease management and to determine the proportions of diabetic patients who achieved the target levels. The association between diabetes duration and each of: treatment strategies, number of complications, comorbidities and clinical outcomes was also evaluated. This was a cross-sectional retrospective observational study involving 1014 patients with type 2 diabetes mellitus who attended the outpatient diabetes clinic at the Penang General Hospital in Malaysia. Each patient’s medical record from 2005 to 2007 was reviewed. The primary and secondary clinical outcomes for treatment of diabetes that are recommended to be monitored include fasting plasma glucose, haemoglobin A1c (HbA1c), blood pressure (BP) and the lipid profile. All the collected data were analysed using the SPSS (version 15.0) software package (SPSS Inc., Chicago, IL) and Microsoft Excel.